2006
DOI: 10.1103/physrevb.74.125102
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy study of the skutteruditesLaFe4Sb12,Ce

Abstract: The electronic structure of the skutterudites CoSb 3 , CoP 3 , LaFe 4 Sb 12 , and CeFe 4 Sb 12 has been investigated with x-ray photoelectron spectroscopy. The binding energies in the pnicogen and transition metal 2p spectra are shifted to reflect changes in the bonding character of these compounds. The asymmetric line shapes in the metal 2p spectra signal electronic delocalization. A plasmon loss satellite peak occurs in the Co 2p spectra of CoSb 3 and CoP 3 . The intensity of this peak in these and other Co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 55 publications
6
24
0
Order By: Relevance
“…For comparison, spectra from Fe 2 O 3 and FeSbO 4 are shown in the inset. The spectrum from as-synthesized CeFe 4 Sb 12 is comprised of 3 main excitations and corresponds to low-spin Fe 2+ , an electronic state that has been proven by previous studies [18,22]. The lowest energy peak in the spectrum (∼7114 eV) represents a pre-edge, Fe 1s → Fe 3d, excitation.…”
Section: Fe K-edge Xanes Spectramentioning
confidence: 89%
See 1 more Smart Citation
“…For comparison, spectra from Fe 2 O 3 and FeSbO 4 are shown in the inset. The spectrum from as-synthesized CeFe 4 Sb 12 is comprised of 3 main excitations and corresponds to low-spin Fe 2+ , an electronic state that has been proven by previous studies [18,22]. The lowest energy peak in the spectrum (∼7114 eV) represents a pre-edge, Fe 1s → Fe 3d, excitation.…”
Section: Fe K-edge Xanes Spectramentioning
confidence: 89%
“…The purity of the synthesized materials was confirmed by powder X-ray diffraction (pXRD) using a Rigaku Rotaflex RU-200 rotating anode X-ray diffractometer. FeSbO4 was phase-pure while CeFe4Sb12 was found to contain a minor concentration of the commonly observed impurity, FeSb2 [12,18].…”
Section: Synthesismentioning
confidence: 96%
“…Due to excellent properties of Co-P compounds, the synthesis technologies have been extensively investigated [16][17][18] and the structural analysis has also been conducted in order to understand the intrinsic mechanism [19][20][21][22][23]. By the linear muffin-tin orbital method in the atomic sphere approximation (LMTO-ASA), it has been found that Co 2 P with hexagonal structure exhibits ferromagnetism while Co 2 P with orthorhombic structure reveals non-magnetic character [19].…”
Section: Introductionmentioning
confidence: 99%
“…In another study on Co-based compounds, [10] the ionic character of the Co-P bond in CoP 3 was further supported by monitoring the intensity of the Co 2p energy loss peak. The observed reduction of the intensity of the loss feature in CoP 3 compared to pure Co was interpreted as a reduction of the Co valence electrons.…”
Section: Resultsmentioning
confidence: 98%